Rethinking outdoor leadership: An Investigation of Affective Abilities in Australian Higher Education curriculum. Issue 3 (2nd July 2020) - Baker, Mandi; O'Brien, Wendy
ABSTRACT: The performance and embodiment of inter and intra-personal skills, or as we have conceptualised in this paper as Affective Abilities (AA), is often considered central to the fulfilment of outdoor leader roles. This article examines Australian outdoor recreation and education higher education curricula to identify what AA training opportunities are provided and prioritised. We performed a content analysis on 47 university subjects/units and all vocational outdoor leadership materials. Our findings suggest that the AA described in curricula can be grouped into five common themes; leadership, facilitation, interpersonal, intrapersonal, and judgement. Reflection was an additional theme within university curricula. We observed that AA are included in curricula but are not always made explicit. Consequently, students may not be aware of what AA they are developing or how to draw on these once in the field. This paper seeks to better understand the AA instructional landscape to aid the development of training programs.